A study on the parameters of exchange enthalpy, X12, and entropy, Q12, in the equation-of-state theory for some polymer-solvent pairs - Yilmaz, F; Cankurtaran, O (ELSEVIER SCI LTD, 1998)
The parameters of exchange enthalpy, X-12, and entropy, Q(12) have been determined for cyclopentane, tetrahydrofurane and 1,4-dioxane with poly(dimethyl siloxane) around room temperature using inverse gas chromatography technique. The parameters X-12 Were compared to the parameters calculated by means of the Berthelot relationship from characteristic pressures of the pure components in the mixtures. The parameters Q(12) were compared to differences of thermal pressure coefficients of the pure components in the mixtures. (C) 1997 Elsevier Science Ltd. All rights reserved.
Keywords: poly(dimethyl siloxane); polymer-solvent interactions; equation of state parameters; POLYSTYRENE SOLUTIONS; THERMODYNAMICS; CYCLOHEXANE; Polymer Science